Beyond Representation: Technofeminisms and the Promise of Computing for Girls. Issue 3 (1st December 2021) - Unknown
Abstract : Kristine Blair. 2019. Technofeminist Storiographies: Women, Information Technology, and Cultural Representation. Lanham, MD: Lexington Books.